AT1 Receptor Gene Polymorphisms in relation to Postprandial Lipemia. (19th September 2011) - Klop, B.; van den Berg, T. M.; Rietveld, A. P.; Chaves, J.; Real, J. T.; Ascaso, J. F.; Carmena, R.; Elte, J. W. F.; Castro Cabezas, Manuel
Abstract : Background . Recent data suggest that the renin-angiotensin system may be involved in triglyceride (TG) metabolism. We explored the effect of the common A1166C and C573T polymorphisms of the angiotensin II type 1 receptor (AT1R) gene on postprandial lipemia. Methods . Eighty-two subjects measured daytime capillary TG, and postprandial lipemia was estimated as incremental area under the TG curve. The C573T and A1166C polymorphisms of the AT1R gene were determined. Results . Postprandial lipemia was significantly higher in homozygous carriers of the 1166-C allele (9.39 ± 8.36  mM * h/L) compared to homozygous carriers of the 1166-A allele (2.02 ± 6.20  mM * h/L) (P < 0.05 ). Postprandial lipemia was similar for the different C573T polymorphisms. Conclusion . The 1166-C allele of the AT1R gene seems to be associated with increased postprandial lipemia. These data confirm the earlier described relationships between the renin-angiotensin axis and triglyceride metabolism.